2020
DOI: 10.1007/978-3-030-57599-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Automatization of Cross-Border Customs Declaration: Potential and Challenges

Abstract: This paper discusses challenges and obstacles of the Estonian customs authority while implementing the new EU VAT directive aiming to raise efficiency in the VAT declaration life-cycle. The general goal of the directive is to reduce cross-border fraud, gain revenue and modernize the system for governments and businesses. Due to the fact that the impact of the new VAT directive is tremendous, it also changes radically AS-IS work routines of customs authorities. The current paper presents the Estonian experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…having a registered legal representative in the EU). Initial case studies on IOSS developments and challenges have already been reported in literature [14]. Other models of engagement have also been envisaged, where the burden for VAT collection is not put on the intermediaries (the eCommerce platforms) but on the parties that are directly engaged in the eCommerce transaction like the buyer and the seller [8].…”
Section: Customs Interactions With Ecommerce Platforms In the Context...mentioning
confidence: 99%
“…having a registered legal representative in the EU). Initial case studies on IOSS developments and challenges have already been reported in literature [14]. Other models of engagement have also been envisaged, where the burden for VAT collection is not put on the intermediaries (the eCommerce platforms) but on the parties that are directly engaged in the eCommerce transaction like the buyer and the seller [8].…”
Section: Customs Interactions With Ecommerce Platforms In the Context...mentioning
confidence: 99%